A driftless gas proportional scintillation counter with a P10 microstrip photosensor in a 5-T magnetic field - Veloso, J. F. C. A. (2002)
The operating characteristics of a xenon driftless gas proportional scintillation counter with a P10 microstrip gas chamber photosensor in magnetic fields up to 5 T are described. Energy resolution of 19% for 2.3-keV X-rays and an equivalent noise of <50 eV were obtained. Pulse amplitude and energy resolution were unaffected from 0 to 5 T, demonstrating the insensitivity of this type of detector to strong magnetic fields.